Weeping in silence: community experiences of stillbirths in rural eastern Uganda - Kiguli, Juliet (Glob Health Action, 2015)
BACKGROUND: Stillbirths do not register amongst national or global public health priorities, despite large numbers and known solutions. Although not accounted in statistics – these deaths count for families. Part of this disconnect is that very little is known about the lived experiences and perceptions of those experiencing this neglected problem. OBJECTIVE: This study aimed to explore local definitions and perceived causes of stillbirths as well as coping mechanisms used by families affected by stillbirth in rural eastern Uganda. DESIGN: A total of 29 in-depth interviews were conducted with women who had a stillbirth (14), men whose wives experienced a stillbirth (6), grandmothers (4), grandfathers (1), and traditional birth attendants (TBAs) (4). Participants were purposively recruited from the hospital maternity ward register, with additional recruitment done through community leaders and other participants. Data were analysed using content analysis. RESULTS: Women and families affected by stillbirth report pregnancy loss as a common occurrence. Definitions and causes of stillbirth included the biomedical, societal, and spiritual. Disclosure of stillbirth varies with women who experience consecutive or multiple losses, subject to potential exclusion from the community and even the family. Methods for coping with stillbirth were varied and personal. Ritual burial practices were common, yet silent and mainly left to women, as opposed to public mourning for older children. There were no formal health system mechanisms to support or care for families affected by stillbirths. CONCLUSION: In a setting with strong collective ties, stillbirths are a burden borne by the affected family, and often just by the mother, rather than the community as a whole. Strategies are needed to address preventable stillbirths as well as to follow up with supportive services for those affected.